PERAN KOPERASI MAISARAH PESANTREN UMMUL AYMAN DALAM MEWUJUDKAN KESEJAHTERAAN DEWAN GURU: The Role of The Maisarah Cooperative, Ummul Ayman Islamic Boarding School, in Realizing The Welfare of The Teacher Council - AL Mustafa , Muhammad (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2023)
In Aceh, Islamic boarding schools have a very special position among the community, so that Islamic boarding schools in Aceh are institutions that easily grow and develop, even now Islamic boarding schools in Aceh have received attention from the government through the Aceh Dayah Education Office. This study aims to examine the role of the Ummul Ayman Islamic boarding school maisarah cooperative in realizing the welfare of the teacher council and the community. The method that the writer uses is qualitative by conducting in-depth interviews. The results of the study show that the role played by the Ummul Ayman Islamic Boarding School to create welfare is to develop the skills of the board of teachers and provide work opportunities for the community within the Islamic boarding school, then make the Maisarah Kopontren a skills laboratory. The implication is being able to minimize economic disparities and develop an Islamic economic system.